Incorporating a fuel cell and energy storage system into microgrid - Lim, Song Hua. (2012)
Many countries which including Singapore are more aware of advantages of introducing different types of system into microgrid. The concept of microgrid is its ability, during a utility grid disturbance, to separate and isolate itself from the utility with little or no disruption to the loads. It also helps to play important parts in the environmental aspects. For instance, it encourages the use of the renewable energy sources, and carbon emissions are reduced. One of the systems that introduced to the mircogrid is the fuel cell system. Fuel cell system is a renewable energy device, which combines hydrogen fuel with oxygen to produce electric power. However, one of the fuel cell limitations is the internal power efficiently, it might not produce a constant output voltage due to its slow response to the load change. This might cause excessive variation of frequency and voltage to the microgrid if the fuel cells fluctuate when connected to the microgrid.